2015
DOI: 10.1188/15.onf.614-624
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Self-Rated Health Status Among Older Adult Cancer Survivors: Does Intensity of Activity Play a Role?

Abstract: Health programs and policies need to address physical activity to improve the overall well-being of older adult cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(50 reference statements)
2
11
1
Order By: Relevance
“…QOL was measured using the EORTC QLQ-C30, which includes global QOL, five functional scales, and multi-and single-item symptom scales on the eighth day following the HCT (Aaronson, Cull, Kaasa, & Sprangers, 1996). This was a secondary data analysis of data from three previous studies (Hacker et al, 2006;Hacker, Larson, Kujath, et al, 2011;. One study was a two-site descriptive study examining fatigue and physical activity following HCT (Hacker et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…QOL was measured using the EORTC QLQ-C30, which includes global QOL, five functional scales, and multi-and single-item symptom scales on the eighth day following the HCT (Aaronson, Cull, Kaasa, & Sprangers, 1996). This was a secondary data analysis of data from three previous studies (Hacker et al, 2006;Hacker, Larson, Kujath, et al, 2011;. One study was a two-site descriptive study examining fatigue and physical activity following HCT (Hacker et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…This was a secondary data analysis of data from three previous studies (Hacker et al, 2006;Hacker, Larson, Kujath, et al, 2011;. One study was a two-site descriptive study examining fatigue and physical activity following HCT (Hacker et al, 2006). Only patients from the University of Illinois Hospital and Health Sciences System were included in the current study because of the inability to gain access to the outside facility's electronic medical record after the initial data collection procedures were completed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Schootman et al, 21 increased participation in LTPA was associated with a reduction of fair-poor self-rated health during both the first year after diagnosis and one year later. In addition, Lee et al 22 found that older adult cancer survivors who engaged in LTPA reported better health status. Moreover, previous studies suggested that LTPA serves an important non-pharmacologic means to improve overall healthrelated quality of life among people with cancer.…”
Section: Leisure Time Physical Activity Health Perception and Mentamentioning
confidence: 99%
“…For example, a population-based study of breast cancer patients found that participation in low-and moderate-intensity LTPA was associated with better mental health (i.e., low levels of depression). 27 Furthermore, Lee et al 22 found the older adult cancer survivors who participated in vigorous LTPA showed significantly higher levels of health status than those who engaged in low-intensity LTPA. These studies suggest that greater involvement in LTPA is positively associated with mental health among people with cancer.…”
Section: Leisure Time Physical Activity Health Perception and Mentamentioning
confidence: 99%